Mechanism of interferon action: autoregulation of RNA-dependent P1/eIF-2 alpha protein kinase (PKR) expression in transfected mammalian cells. - Thomis, D C (1992)
The expression of a molecular cDNA clone (P1 KIN) of the human RNA-dependent P1/eIF-2 alpha protein kinase (PKR) was examined in transfected monkey cells and in cell-free protein-synthesizing systems. Expression of the wild-type (wt) P1 KIN cDNA, which encodes an active protein kinase, was compared with that of the phosphotransfer catalytic domain II Lys-296-->Arg (K296R) mutant cDNA, which does not encode an active kinase. wt and K296R mutant P1 mRNAs prepared by transcription in vitro with T7 RNA polymerase programmed the cell-free synthesis of P1 ribosome-associated protein with comparable efficiency in the rabbit reticulocyte system. The K296R mutant P1 protein was also efficiently synthesized in vivo in transfected COS monkey cells. However, synthesis of the wt P1 protein was reduced about 30-fold in transfected COS cells as compared with the K296R mutant P1 protein. Cotransfection of wt P1 KIN cDNA with either K296R mutant P1 KIN cDNA or reovirus S4 cDNA greatly reduced the synthesis of K296R mutant P1 protein and reovirus sigma 3 protein, respectively. Although the wt and K296R mutant P1 KIN plasmid expression vectors replicated with comparable efficiencies in COS cells, the steady-state amount of P1 mRNA was about 3-fold less in COS cells transfected with the wt as compared with the K296R mutant P1 KIN cDNA. These results suggest that RNA-dependent P1 protein kinase expression is autoregulated in vivo in transfected mammalian cells primarily at the level of translation by a mechanism that is likely dependent upon catalytically active P1 kinase.